2009
DOI: 10.2169/internalmedicine.48.1251
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-Like Oxidized LDL Receptor-1 (LOX-1) Expression in the Tubulointerstitial Area Likely Plays an Important Role in Human Diabetic Nephropathy

Abstract: Objective Diabetic nephropathy (DN) is a common cause of end

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…This was also noted to be the pathway by which OxLDL activation of AngII=R leads to Smad activation. TGF-b, angiotensin II (Ang II), and ischemia can upregulate tubulointerstitial LOX-1 expression, further enhancing deleterious effects of OxLDL on tubulointerstitum ultimately leading to fibrosis (307).…”
Section: Oxldl In Diabetes Mellitusmentioning
confidence: 99%
“…This was also noted to be the pathway by which OxLDL activation of AngII=R leads to Smad activation. TGF-b, angiotensin II (Ang II), and ischemia can upregulate tubulointerstitial LOX-1 expression, further enhancing deleterious effects of OxLDL on tubulointerstitum ultimately leading to fibrosis (307).…”
Section: Oxldl In Diabetes Mellitusmentioning
confidence: 99%
“…The OLR-1 up-regulation in the kidney of Dahl salt-sensitive rats was parallel to glomerulosclerotic changes and renal dysfunction, suggesting a possible pathogenetic role for renal OLR-1 in the progression to hypertensive glomerulosclerosis (Nagase et al, 2000). In subjects with diabetic mellitus, increased expression of OLR-1 mRNA in the tubulointerstitial area may be closely linked to the development and progression of diabetic nephropathy and tubulointerstitial damage (Yamamoto et al 2009). The role of OLR-1 in the development of angiotensin II-induced hypertension and subsequent renal damage was recently reported (Hu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic nephropathy (DN) is a common cause of endstage renal disease [1] . Tubular dysfunction has been reported in patients with diabetes mellitus in the absence of microalbuminuria, suggesting a pivotal role of tubulo-interstitium in the development of DN [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates that LOX-1 plays an important role in the pathogenesis and progression of DN [1,5] . It has been reported that LOX-1 is strongly expressed in the kidneys of obese diabetic rats, and its expression parallels renal dysfunction [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%